Metagenomic profiling of the pro-inflammatory gut microbiota in ankylosing spondylitis. Issue 107 (February 2020) - Zhou, Chen; Zhao, Hui; Xiao, Xin-yue; Chen, Bei-di; Guo, Rui-jin; Wang, Qi; Chen, Hua; Zhao, Li-dan; Zhang, Chen-chen; Jiao, Yu-hao; Ju, Yan-mei; Yang, Hua-xia; et al.
Abstract: Objective: Gut dysbiosis has been reported implicated in ankylosing spondylitis (AS), a common chronic inflammatory disease mainly affects sacroiliac joints and spine. Utilizing deep sequencing on the feces of untreated AS patients, our study aimed at providing an in-depth understanding of AS gut microbiota. Methods: We analyzed the fecal metagenome of 85 untreated AS patients and 62 healthy controls by metagenomic shotgun sequencing, and 23 post-treatment feces of those AS patients were collected for comparison. Comparative analyses among different cohorts including AS, rheumatoid arthritis and Behcet's disease were performed to uncover some common signatures related to inflammatory arthritis. Molecular mimicry of a microbial peptide was also demonstrated by ELISpot assay. Results: We identified AS-enriched species including Bacteroides coprophilus, Parabacteroides distasonis, Eubacterium siraeum, Acidaminococcus fermentans and Prevotella copri . Pathway analysis revealed increased oxidative phosphorylation, lipopolysaccharide biosynthesis and glycosaminoglycan degradation in AS gut microbiota. Microbial signatures of AS gut selected by random forest model showed high distinguishing accuracy. Some common signatures related to autoimmunity, such as Bacteroides fragilis and type III secretion system (T3SS), were also found. Finally, in vitro experiments demonstrated an increased amount of IFN-γ producing cells triggered by a bacterial peptide of AS-enriched species, mimicking type II collagen. Conclusions: These findings collectively indicate that gut microbiota was perturbed in untreated AS patients with diagnostic potential, and some AS-enriched species might be triggers of autoimmunity by molecular mimicry. Additionally, different inflammatory arthritis shared some common microbial signatures. Highlights: Gut microbiota was perturbed in untreated ankylosing spondylitis patients. Distinctive species and pathways were found and correlated with clinical indices. A diagnostic classifier was made based on differently expressed gut microbes. Common gut microbial signatures of inflammatory arthritis were revealed. A microbial peptide can trigger IFN-γ secretion by mimicking type II collagen.